Solar Powered Water Level Monitoring System for Flood Management in Rural Area using GSM Module - Daminon, Eldievant; Yaacob, Maslina (Evolution in Electrical and Electronic Engineering, 2024)
The present natural disasters such as floods cause loss of life, property, devastation of livestock and agriculture. Flood is known as yearly disaster in Malaysia because of the monsoon season that will cause heavy rain in certain states, especially at Sabah. Therefore, the system develops a solar powered water level monitoring system for flood management and notify the user by using the GSM module. The notification messages will be sent to cellular of logged user that are head of village and people at the affected areas. The system uses three Ultrasonic Sensors, Buzzer, Solar power, Buzzer, Arduino UNO, ESP32 and GSM shield as the main components in the prototype. Arduino UNO and the ESP32 act as micro-controllers of systems to perform various actions such as observe height of water and perform calculation and send SMS through GSM shield. This system successfully measured the water level with 99.58% success accuracy for the first sensor, 99.59% success accuracy for the second sensor and 99.53% success accuracy for the third sensor. With a few hours, the solar also managed to charge the battery for the system. Moreover, with 96.67% accuracy of GSM test success rate, it successfully sends SMS to the user if the water level is in danger condition. However, data collection for flood management involving message transmission time and sensor reading distance is one of the scope systems. Thus, with the availability of this effective SMS flood notification system, people can take immediate action and take more precautions to save lives and reduce damage due to flood disasters, especially in low-lying areas in rural villages that are far from internet access.